Comportamento cinético do cloro livre em meio aquoso e formação de subprodutos da desinfecção - Ferreira Filho, Sidney Seckler; Sakaguti, Mariane [UNESP] (FapUNIFESP (SciELO), 2008)
One indirect approach to predict the disinfection by-product (DBP) formation potential for a given water source is by evaluation of the kinetic behavior of free chlorine in the liquid phase and chlorine demand determination for different operation conditions of the chlorination process. The objective of this work was to evaluate the kinetic behavior of free chlorine in water or a number of different raw water sources, as well as to investigate the impact of the coagulation process on chlorine demand reduction and DBP formation. It was observed that the higher the total organic carbon (TOC) removal efficiency through coagulation, the lower the liquid phase chlorine demand. Regarding trihalomethane (THM) formation, a ratio of 28 ug/L formed per mg/L of applied chlorine was observed for the waters employed in the experimental investigation.
Kinetic behavior of free chlorine in the liquid phase and disinfection by-product (DBP) formation
Keywords: Chemical kinetics; Chlorine; Disinfection byproducts; Water treatment